Assessment of dermal fibrosis. (1st October 2019) - Ud‐Din, S.; Foden, P.; Stocking, K.; Mazhari, M.; Al‐Habba, S.; Baguneid, M.; McGeorge, D.; Bayat, A.
Summary: The wound healing process can result in the formation of a scar, which replaces normal tissue after injury. Many scar treatments are available but none can totally erase a scar and many can result in a poor outcome. Therefore, in order to evaluate current treatments, as well as research to develop new methods for treating scars, devices which give numerical values at each stage of wound healing are needed. Assessing skin fibrosis (scarring) remains a challenge. This study therefore aimed to find out if high frequency ultrasound (HFUS) and optical coherence tomography (OCT) devices were able to provide a numerical indicator (score) of skin fibrosis over the course of wound healing. This was achieved by recruiting 62 healthy volunteers in Manchester, United Kingdom and carrying out small skin biopsies to their upper inner arms over eight weeks. They had measurements taken each week by HFUS and OCT and this was supported by laboratory analysis. Both devices were able to provide numerical measurements for skin thickness and this was shown to be similar to laboratory measurements. The device software also gave measurements that linked with the amount of collagen in the skin (which gives skin its structure). This was supported by laboratory analysis of different types of collagen. Both techniques were able to identify different structures within the skin but at different depths and resolutions depending upon which device was used. Skin structures were better seen by OCT due to the resolution, whilst HFUS allowed the researchers to see the deeper skin layers. In conclusion, the choice of device is important as this would depend on the type, size and depth of the wound or scar, and specific factors to be investigated or monitored.